Active log periodic antenna - A. Rahim, Mohamad Kamal (Penerbit UTM Press, 2007)

(untitled)
This paper describes four different configurations of active devices integration into log periodic antennas (LPAs). The first configuration involves the integration of a single amplifier at the input feed line of a five element log periodic antenna (LPA). The second configuration involves the integration of an amplifier in the middle of the five elements LPA. The third configuration is the five element LPA with individual amplifiers in each element. The last configuration involves the integration of the individual amplifiers and filters with five element LPA in each element. The performance of these configurations have been investigated and compared in terms of the bandwidth, gain relative to a passive LPA, cross polar isolation and half power beamwidth.